Pharmacological Potential of Flavonoids against Neurotropic Viruses - Juliana Helena Castro e Silva; Jéssica Teles Souza; Clarissa Schitine; Aníbal de Freitas Santos Júnior; Eduardo Muniz Santana Bastos; Silvia Lima Costa (MDPI AG, 2022)
Flavonoids are a group of natural compounds that have been described in the literature as having anti-inflammatory, antioxidant, and neuroprotective compounds. Although they are considered versatile molecules, little has been discussed about their antiviral activities for neurotropic viruses. Hence, the present study aimed to investigate the pharmacological potential of flavonoids in the face of viruses that can affect the central nervous system (CNS). We carried out research from 2011 to 2021 using the Pubmed platform. The following were excluded: articles not in the English language, letters to editors, review articles and papers that did not include any experimental or clinical tests, and papers that showed antiviral activities against viruses that do not infect human beings. The inclusion criteria were in silico predictions and preclinical pharmacological studies, in vitro, in vivo and ex vivo, and clinical studies with flavonoids, flavonoid fractions and extracts that were active against neurotropic viruses. The search resulted in 205 articles that were sorted per virus type and discussed, considering the most cited antiviral activities. Our investigation shows the latest relevant data about flavonoids that have presented a wide range of actions against viruses that affect the CNS, mainly influenza, hepatitis C and others, such as the coronavirus, enterovirus, and arbovirus. Considering that these molecules present well-known anti-inflammatory and neuroprotective activities, using flavonoids that have demonstrated both neuroprotective and antiviral effects could be viewed as an alternative for therapy in the course of CNS infections.